2020
DOI: 10.1111/ivb.12277
|View full text |Cite
|
Sign up to set email alerts
|

General characterization of regeneration in Aeolosoma viride (Annelida, Aeolosomatidae)

Abstract: Regeneration has long been the focus of scientific interest for its potential to restore lost, damaged, or aged tissues and organs. A wide range of regenerative studies have been conducted on different vertebrate and invertebrate model organisms. Annelids are known for their regenerative capacities, and because of their relatively complex organ systems, they are an ideal organism for regeneration study. Our present work focused on the freshwater annelid Aeolosoma viride, an asexually reproducing annelid capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Through the release of hormones, the brain promoted or inhibited regeneration in some annelids 12 , 37 . It was previously reported that no further replacements occurred after K-type jaws formed in Ophryotrocha 1 , 38 , 39 . Thus, more details about the molecular mechanisms between posterior and anterior regeneration in O. xiamen is needed to better understand the essential foundation for future mechanistic and comparative studies of regeneration.…”
Section: Discussionmentioning
confidence: 86%
“…Through the release of hormones, the brain promoted or inhibited regeneration in some annelids 12 , 37 . It was previously reported that no further replacements occurred after K-type jaws formed in Ophryotrocha 1 , 38 , 39 . Thus, more details about the molecular mechanisms between posterior and anterior regeneration in O. xiamen is needed to better understand the essential foundation for future mechanistic and comparative studies of regeneration.…”
Section: Discussionmentioning
confidence: 86%
“…However, in this study, we observed that O. xiamen could form one or two new segments forward but no complete head region, including eye and antennae. Presumably, the lower percentage of successful regenerates in anterior regeneration can be attributed to the need for restoration of more complex structures including the brain, eye, and jaw [12,26,32]. Further work is needed to better understand the essential foundation for future mechanistic and comparative studies of regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The RNAi protocol was modified as described previously 2 . Double stranded RNA (dsRNA) was synthesized according to E-RNAi -a web application used to design optimized RNAi construct 64 .…”
Section: Whole Mount In Situ Hybridization (Wmish)mentioning
confidence: 99%